2019
DOI: 10.1002/hpm.2858
|View full text |Cite
|
Sign up to set email alerts
|

Improving mental healthcare for the elderly in Belgium

Abstract: Summary Introduction The organisation of mental healthcare for the elderly (MHCE) remains suboptimal. Objective To identify specific organisational models that could address the mental healthcare needs of the elderly in community and primary care. Method A multi‐modal approach, consisting of a literature review, an online survey of Belgian professional stakeholders, and an international comparison. The outcomes of this three‐step study process were aggregated. Results Two general and four operational strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…These findings are reinforced by results of Butu et al ( 30 ), where 55% of the Romanian GPs investigated have reported to have rarely or never asked advice from a psychiatrist or have met them face to face. Our results are also similar with those of studies conducted in other countries which highlight that, in general, GPs are willing to initiate and provide treatment for mental health problems if they would have better collaborative relationships with mental health specialists ( 33 35 ). For example, a study conducted in France found out that a minority of GPs had a satisfactory relationship with private psychiatrists (49.5%) and public psychiatrists ( 36 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are reinforced by results of Butu et al ( 30 ), where 55% of the Romanian GPs investigated have reported to have rarely or never asked advice from a psychiatrist or have met them face to face. Our results are also similar with those of studies conducted in other countries which highlight that, in general, GPs are willing to initiate and provide treatment for mental health problems if they would have better collaborative relationships with mental health specialists ( 33 35 ). For example, a study conducted in France found out that a minority of GPs had a satisfactory relationship with private psychiatrists (49.5%) and public psychiatrists ( 36 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, in an ideal context where current barriers would be surpassed, the GPs expect an increase of these skills of up to 25%, which represent an encouraging result. Previous studies also highlight the fact that GPs are well-positioned to address MHP in their older patients because of (a) their long-lasting bond with their older patients, (b) their holistic view of the patient, and (c) the easy low-threshold access they offer, but the lack of knowledge, skills, and confidence in their skills can substantially impair detection as well as treatment ( 33 ). In Romania, interventions for increasing the skills of GPs have been implemented in the last decades but these were project based and did not lead to systemic changes in the initial training of GPs, in the Continuing Medical Education (CME) programs or in the financial incentive structure.…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of older people with mental disorders live at home and are cared for by their relatives, which requires the involvement of primary care physicians and rapid intervention ( Adriaenssens et al, 2019 ). Whenever possible and when required by the patient, the patient should be assessed and cared for in their own environment, limiting trips to health centers for emergencies or seriousness, or for special tests ( Snowdon, 2007 ).…”
Section: Introductionmentioning
confidence: 99%